Parental involvement in school-related work of fourth grade public school pupils from an urban poor community - Punto, Samantha S.
This study explores the parental involvement in school-related work of fourth grade children from an urban poor community. Practices of both mothers and fathers are described and analyzed to further understand their involvement in their children's school-related work, which include doing assignments, making projects, and studying for exams. Rules and expectations of the parents are also specified, as well as the facilitating and limiting factors that parents have in involving in their fourth grade children's school work. Furthermore, the similarities and differences of the involvement of mothers and fathers are also determined. Thirty couples, or fifteen mothers and fifteen fathers from an urban poor community in Diliman, Quezon City were the chosen participants. a semi-structured interview was used to gain information and data useful for this study. Results show that generally, parents are involved in their fourth grade children's school-related work. However, the mothers' availability allow them to be more actively involved than the fathers whose occupations serve as a limiting factor for them to be aware of and to involve in their children's study habits.